2006
DOI: 10.1111/j.1556-4029.2006.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Dilemma of Sudden Deaths Due to Acute Hemorrhagic Pancreatitis

Abstract: Sudden death due to acute pancreatitis has been rarely determined. A review of 3305 autopsies performed between 1991 and 2001 at the Council of Forensic Medicine found 12 cases (0.36%) with sudden death due to acute hemorrhagic pancreatitis without symptoms. A history of chronic alcohol ingestion was obtained from family in four cases (33%), and no stones were found in the bile ducts or in the gall bladders. During the autopsies, hemorrhage and edema were localized on the head of the pancreas in three cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Interestingly, first episodes of AP, which have higher mortality rates than multiple episodes of AP, [2] was pathologically depicted in this case. Pulmonary edema, which has been considered a major organ failure and an early cause of death in individuals with SAP in both clinical- and autopsy-based studies, [2,5,3133] was also found in this case. SAP-induced severe systemic inflammatory response, [32] diabetic ketoacidosis, [34] fluid overload, and/or blood transfusion [35] could be responsible for such a phenomenon.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, first episodes of AP, which have higher mortality rates than multiple episodes of AP, [2] was pathologically depicted in this case. Pulmonary edema, which has been considered a major organ failure and an early cause of death in individuals with SAP in both clinical- and autopsy-based studies, [2,5,3133] was also found in this case. SAP-induced severe systemic inflammatory response, [32] diabetic ketoacidosis, [34] fluid overload, and/or blood transfusion [35] could be responsible for such a phenomenon.…”
Section: Discussionsupporting
confidence: 53%
“…The haemorrhage was confined to the head of the pancreas in three cases and involved the whole body in nine. While pulmonary congestion and haemorrhages were also found, no association between the two was established 22. Our series enrolled only sudden nocturnal death, hence dealing with a more specific population.…”
Section: Discussionmentioning
confidence: 96%
“…A range of esophageal causes of sudden death have been recorded [310] including in relation to megaesophagus [311]; esophageal polyps [312]; hemorrhage from varices, vascular abnormalities or Mallory-Weiss tears, and rupture, which may be spontaneous (Boerhaave syndrome) [313] or secondary to conditions such as Barrett's esophagus [314]. Within the abdominal cavity, acute hemorrhage from peptic ulcer or dissecting aneurysm [281], perforated peptic ulcer [20,315], rupture of the stomach [316], perforated colon (diverticular or stercoral from constipation [317]), intestinal obstruction, intussception [318], mesenteric ischemia, acute pancreatitis [319,320], acute cholecystitis and fatty liver may be responsible for sudden death [321]. However, it must be remembered that esophageal and gastric rupture can occur due to resuscitative techniques (including the Heimlich manoeuver) [322][323][324] and intussception can be a terminal event not related to the cause of death [325].…”
Section: Gastrointestinal Pathologies That May Present As Sudden Deathmentioning
confidence: 99%